Pengaruh asuransi kesehatan nasional terhadap pengeluaran kesehatan pada penduduk lanjut usia di Indonesia - Chrisnahutama, Adrian (Nur Science Institute, 2023)
This study aims to analyze the effect of ownership or access to national health insurance, namely National Health Insurance (JKN), on health expenditure among the elderly population in Indonesia. This study uses cross-section data from the 2019 Socio-Economic Survey (Susenas). This study found that older adults with JKN have health expenditures that are 0.110 percentage points higher than older people who do not have JKN. Furthermore, national health insurance ownership is unrelated to health expenditure among poor older adults. The result shows that JKN has not been utilized as financial protection for the elderly when accessing health services.